The cultural preparation of scholarship students within the scholarship program by the Custodian of the Two Holy Mosques from their perspective: An empirical study - Altwejery, Ebtesam AbdulAziz; Alahmad, Hind Mohammed (Journal of Educational and Psychological Sciences, 2022)
The purpose of this study was to explore the reality of the cultural preparation for scholarship students by the Custodian of the Two Holy Mosques program for external scholarship، its obstacles، and the suggestions that contribute to improve it from their perspectives. All scholarship students by the program of the Custodian of the Two Holy Mosques program for external scholarship، amounting to (161285) students، and the researcher chose a sample by random method، and the sample size was (500) students، representing 0.3% of the total population of the study. The most prominent results of the study were: the scholarship students agreed that the cultural preparation of scholarship students by the Custodian of the Two Holy Mosques program for external scholarships، from their perspectives ،was moderate، while to a large extent they agreed all the cultural preparation obstacles for scholarship students by the Custodian of the Two Holy Mosques program for external scholarship، and presented a number of suggestions that develope the preparation programs which provided by the Ministry of Education for scholarship students، also it demonstrated the absence of a statistically significant difference between the responses of the study sample members towards the cultural preparation of scholarship students and its obstacles due to the different variables (gender، age، degree، scholarship year، exit from the Kingdom of Saudi Arabia - the countries visited by the scholarship holder).The study recommended a number of recommendations، the most important of the recommendations was the adoption of the Islamic culture for scholarship students as a prerequisite for passing the acceptance stage of the scholarship، and inform scholarship students about the intellectual challenges that they may face in the country of the scholarship.
Keywords: Cultural preparation; External scholarship; Scholarships